Implementasi Model Problem-Based Learning pada Mata Pelajaran Dasar-Dasar Teknik Ketenagalistrikan - Hafifah, Agnestasya Zahara; Pulungan, Ali Basrah (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
The achievement of learning outcomes of students in class X TKL 2 at SMK Negeri 1 Sumatera Barat in the subject of Basic Electricity Engineering is still disappointing with 20 people below the KKM out of a total of 36 students. One of the causes is the teacher-centered learning process so that students become passive. Therefore, it is necessary to conduct research with the implementation of the Problem-Based Learning model to analyze the effect on student competence in the cognitive domain. This research is an experimental study categorized into the type of pre-experimental research with a one-group pretest post-test design. The subjects of this study were students of class X TKL 2 SMK Negeri 1 Sumatera Barat in the 2023/2024 school year consisting of 35 students. To analyze, a pretest was given before the implementation of Problem-Based Learning to measure students' initial abilities. Then the posttest was given after the learning process of Basic Electricity Engineering was applied to the Problem-Based Learning model. The pretest and posttest results will be analyzed using classical completeness testing and effect size. Based on the research results, it shows that the students' scores after applying the Problem-Based Learning model are higher than the students' scores before applying the Problem-Based Learning model. The results of classical completeness testing and effect size show that as much as the implementation of the Problem-Based Learning model can improve student learning outcomes.